TAYUBAN DALAM TRADISI SAPARAN DI KELURAHAN TEGALREJO, KECAMATAN ARGOMULYO, KOTA SALATIGA - Fandy Aprianto Rohman (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2019)
Tegalrejo is the only sub-district in Salatiga that still preserves the tayuban, a traditional dance where men dance directly with women. The dance is performed each year as the climax in the village cleansing ceremony of the Saparan festival. The tayuban, which is an important function in the ceremony, has been passed down from generation to generation is well maintained by the people of Tegalrejo sub-district. The tayuban also functions as an entertainment for the local people. This qualitative research aims to describe the tayuban and its elements. The data were collected from interviews, observation, and available documents. The research has found that the elements of the tayuban include ledhek (female dancers), pengrawit (gamelan musicians), penjanggrung (men who dance together with ledheks), and offerings.